2018
DOI: 10.1029/2017jd027386
|View full text |Cite
|
Sign up to set email alerts
|

Lidar Observations of Stratospheric Gravity Waves From 2011 to 2015 at McMurdo (77.84°S, 166.69°E), Antarctica: 2. Potential Energy Densities, Lognormal Distributions, and Seasonal Variations

Abstract: Five years of Fe Boltzmann lidar's Rayleigh temperature data from 2011 to 2015 at McMurdo are used to characterize gravity wave potential energy mass density (Epm), potential energy volume density (Epv), vertical wave number spectra, and static stability N2 in the stratosphere 30–50 km. Epm (Epv) profiles increase (decrease) with altitude, and the scale heights of Epv indicate stronger wave dissipation in winter than in summer. Altitude mean Etrue¯pm and Etrue¯pv obey lognormal distributions and possess narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
80
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(92 citation statements)
references
References 65 publications
9
80
3
Order By: Relevance
“…The modeling results suggest a first‐order mechanism that the equatorial QBO affects the mean wind in the polar region and then alters the efficiency of extracting energy from the mean wind to generate EPWs, thereby imposing the QBO signal onto the polar EPWs. Chu et al () have shown that potential energy densities of stratospheric gravity waves observed at McMurdo, Antarctica, are larger in 2012 and 2015 winters than 2011, 2013, and 2014, which is opposite to EPW1 interannual variability. Such QBO‐like signature in gravity waves is likely caused by the filtering effect of the PNJ (X. Chu, private communication, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The modeling results suggest a first‐order mechanism that the equatorial QBO affects the mean wind in the polar region and then alters the efficiency of extracting energy from the mean wind to generate EPWs, thereby imposing the QBO signal onto the polar EPWs. Chu et al () have shown that potential energy densities of stratospheric gravity waves observed at McMurdo, Antarctica, are larger in 2012 and 2015 winters than 2011, 2013, and 2014, which is opposite to EPW1 interannual variability. Such QBO‐like signature in gravity waves is likely caused by the filtering effect of the PNJ (X. Chu, private communication, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…However, a large-amplitude mesospheric mountain wave with 67 K peak-to-peak amplitude was observed by ground-based lidar for a short duration of 2 h above Lauder, New Zealand, which is also a gravity wave hot spot 35 , 36 . At southern high latitudes, intra-annual and seasonal gravity wave statistics are available from a number of lidar stations in Antarctica 22 25 . They all indicate increased gravity wave activity during winter, but likely do not capture the strongest events due to their location within the polar vortex.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Therefore, our lead question is: can local, continuous and high-temporal-and high-vertical-resolution observations of gravity waves in the lee of the Andes enhance our knowledge about the magnitude of the momentum that is deposited in the stratosphere? Such observations can be accomplished using powerful, vertically-pointing Rayleigh lidars as operated at few locations world-wide [21][22][23][24][25][26][27] . To specifically target the worlds's largest gravity waves, we installed the Compact Autonomous Rayleigh lidar (CORAL) at Rio Grande, Tierra del Fuego, Argentina, for night-time measurements of atmospheric temperature.…”
mentioning
confidence: 99%
“…They propagate in all azimuths except perpendicular to the body force direction. For those that propagate upward, their amplitudes increase exponentially with height, thereby enabling them to have important influences on the upper atmosphere and ionosphere (Becker & Vadas, ; Bossert et al, ; Chu et al, ; de Wit et al, ; Fritts et al, ; Heale et al, ; Liu & Vadas, ; Vadas et al, ; Vadas & Becker, ; Vadas & Liu, , ; Watanabe & Miyahara, ; Zhao et al, ). Thus, it is important to characterize both the primary GWs and LSWs in both observations and model simulations.…”
Section: Introductionmentioning
confidence: 99%